Revitalisasi PAUD melalui Program KKN Melayu Serumpun di Desa Sembuang: KKN Melayu Serumpun - Ayu Ningsih, Risti; Farhan, Muhammad; Unaisa, Siti; Zahara, Maulia; Atika, Filza; Dewi, Rosna; Agista, Tasya; Ardilla, Diana; Rizal, Muhammad; Syarifuddin, Syarifuddin; Nuhdillah, Alwan; Rahma, Ainur; Septiawan, M. Kiki; Helmi, Ahmat Su (LSM Catimore dan Sahabat, 2024)
This study aims to evaluate the impact of the revitalization of Early Childhood Education (PAUD) in Sembuang Village, East Aceh, through the Melayu Serumpun Community Service Program (KKN). The PAUD experienced a decline in student numbers and eventually ceased operations for a year due to the neglected and unattractive physical environment for children. This condition led to a decrease in children's interest in attending school. The revitalization program carried out by KKN students aimed to improve the physical condition of the PAUD and rekindle children's enthusiasm for learning in the village. The revitalization steps included cleaning the school area, repairing facilities, and decorating classrooms with educational decorations to create a more engaging and conducive learning environment. This research employs a qualitative method with a descriptive-analytical approach, conducted from July 25, 2024, until the end of the KKN period. Data were collected through interviews with PAUD teachers, parents, the community, and KKN students, as well as direct observations and documentation of the revitalization activities. The analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study showed a significant increase in the number of children attending PAUD after the revitalization, from 10 children before the program to 25 children afterward. Additionally, the active involvement of the community in physical projects such as the creation of waste bins and the construction of stairs highlighted their high level of participation, which was a key factor in the success and sustainability of the revitalization program. Community participation not only accelerated the implementation of the revitalization but also enhanced the sense of ownership and responsibility for early childhood education in Sembuang Village.